Front Cover: Structures in Tetrahydrofolate Methylation in Desulfitobacterial Glycine Betaine Metabolism at Atomic Resolution (ChemBioChem 6/2020). (26th February 2020) - Badmann, Thomas; Groll, Michael
Abstract : Enzymes that orchestrate methylation between tetrahydrofolate (THF) and cobalamin are abundant among all domains of life. During the energy‐producing catabolism of glycine betaine in Desulfitobacterium hafniense, MtgA catalyzes methyl transfer from methylcobalamin to THF. Atomic insights into the substrate–enzyme interactions of MtgA and THF as well as analysis of a trapped (THF‐CH3 ) + reaction intermediate in sp 3 hybridization reveal a unique binding mode for the THF glutamyl‐ p ‐aminobenzoate moiety during methyl transfer. More information can be found in the communication by M. Groll and T. Badmann on page 776 in Issue 6, 2020 (DOI: 10.1002/cbic.201900515 ).